KEANEKARAGAMAN BURUNG (AVIFAUNA) DI AREA KEBUN GEDUNG SBSN DAN MA’HAD AL-JAMIAH UIN MATARAM - Sukmin; Ditiyyah Hafidzah; Roshiyah Hilyatiy; Muhammad Zulhariadi (Universitas Nias Raya, 2025)
This study was conducted to explore the diversity of bird species (avifauna) in the garden area surrounding the SBSN Building and Ma’had Al-Jamiah at the State Islamic University (UIN) Mataram. A quantitative descriptive method was employed, using the Point Count technique—a method for recording individual birds detected either visually or by sound from specific observation points. Observations were carried out intensively over three days, during both morning and afternoon sessions, to obtain more representative data. The results revealed a total of 74 individual birds, comprising 5 species from 5 different families. The calculated Shannon-Wiener diversity index (H’) was 1.18, indicating a moderate level of species diversity. The evenness index (E), with a value of 0.74, suggests that the distribution of individuals among species was relatively balanced. Meanwhile, the dominance index (C) was 0.35, reflecting a moderate level of species dominance as well. Overall, the findings indicate that the garden area around the campus provides a relatively stable ecosystem that supports the presence of wild birds. Therefore, this area holds significant potential to be developed as a conservation zone and a biodiversity preservation site within the educational environment.